Persistent left superior vena cava in a 29-year-old lady with Ebstein's anomaly and complete heart block. A case report and literature review. (June 2022) - Russell, J.B.W.; Koroma, T.R.; Conteh, V.; Coker, J.; Conteh, S.; Bharat, Kumar; Mahdi, O.Z.
Abstract: Introduction: Persistent Left Superior Vena Cava (PLSVC) is a rare congenital vascular anomaly that may occur alone or in combination with complex congenital heart anomalies and dangerous arrhythmias. We report the first case in the literature of combined PLSVC, Ebstein's Anomaly (Type A) and complete atrioventricular block in an adult female, being successfully managed with permanent pacemaker implantation in Sierra Leone. Case summary: We present an interesting case of a 29-year-old female, referred to the cardiology clinic on account of breathlessness, dizziness, and recurrent syncope. Physical examination revealed a pulse rate of 39 bpm, jugular venous pulse with occasional cannon waves, and grade 3/6 pansystolic murmur in the tricuspid valve area. An electrocardiogram confirmed complete atrioventricular block with junctional escape rhythm, while Transthoracic Echocardiogram (TTE) confirmed Ebstein's Anomaly (Type A) and moderate tricuspid regurgitation. PLSVC was discovered as an incidental intraprocedural finding. Deploying a pacemaker lead through this venous anomaly from the left side was futile. Nevertheless, we used a right sided approach that resulted in a successful permanent pacemaker implantation with optimal and stable parameters. Conclusion: This rare case report highlights the practical challenges often encountered in the practice of cardiology during pacemaker and other cardiac device implantation. Cardiologists and critical care physicians should be acquainted with the venous anomaly of PLSVC, its variants, and procedure-associated risks, for better clinical decision making. Highlights: Persistent left superior vena cava (PLSVC) is a rare congenital venous anomaly, with clinical relevance of congenital heart disease and cardiac conduction abnormalities. Although PLSVC is usually asymptomatic, it is mostly diagnosed as an incidental intraprocedural finding and may complicate cardiac device implantation. To the best of our knowledge, we are the first to report in the literature a case of combined PLSVC, Ebstein's Anomaly and complete heart block in an adult, being successfully managed with permanent pacemaker. This rare case report highlights the practical challenges encountered during permanent pacemaker implantation when using fluoroscopic C-arm X-ray machine as a radio-imaging instrument.